2015
DOI: 10.1002/acn3.173
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated multimodal hubs and seizures in temporal lobe epilepsy

Abstract: ObjectiveBrain connectivity at rest is altered in temporal lobe epilepsy (TLE), particularly in “hub” areas such as the posterior default mode network (DMN). Although both functional and anatomical connectivity are disturbed in TLE, the relationships between measures as well as to seizure frequency remain unclear. We aim to clarify these associations using connectivity measures specifically sensitive to hubs.MethodsConnectivity between 1000 cortical surface parcels was determined in 49 TLE patients and 23 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 66 publications
2
43
0
Order By: Relevance
“…The invasive intracranial EEG is supposed to be useful for the surgical localization of epileptic foci in patients with intractable epilepsy; the data on safety and surgical outcome with this technique are still inadequate [8][9][10][11]. The ample evidences of advanced research using multimodal combinational non-invasive neuroimaging techniques like MRI, MRS, f-MRI, FDG-PET, SPECT, and MEG have revealed that most of the cases of TLE patients are accompanied by pathological changes in brain structure and function network, including cortical and subcortical (hippocampus and parahippocampus) structures [12][13][14]. Such multimodal combinational imaging (structural and functional) approaches are being suggested to detect the laterization of TLE with ictal and interictal onset in pre-surgical diagnostic purpose [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…The invasive intracranial EEG is supposed to be useful for the surgical localization of epileptic foci in patients with intractable epilepsy; the data on safety and surgical outcome with this technique are still inadequate [8][9][10][11]. The ample evidences of advanced research using multimodal combinational non-invasive neuroimaging techniques like MRI, MRS, f-MRI, FDG-PET, SPECT, and MEG have revealed that most of the cases of TLE patients are accompanied by pathological changes in brain structure and function network, including cortical and subcortical (hippocampus and parahippocampus) structures [12][13][14]. Such multimodal combinational imaging (structural and functional) approaches are being suggested to detect the laterization of TLE with ictal and interictal onset in pre-surgical diagnostic purpose [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…It is unclear whether these changes reflect a chronic effect of the disease on brain connectivity or whether they are an index of acute seizure burden 3; 4 . Epilepsy surgery is a potential therapeutic option for patients with medically intractable epilepsy that in many patients can drastically reduce seizure burden 5; 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It is acquired at a resting state of the subject without requiring any tasks. Over a couple of decades, there have been increasing interests in the application of this method for understanding the brain networks in both healthy subjects and patients with neuropsychiatric diseases, e.g., Alzheimer's disease, schizophrenia and epilepsy (9,10,11). Here, we review the technique and the applications of RS-fMRI for evaluating the language function, and discuss combining functional and structural connectivity analyses.…”
Section: Introductionmentioning
confidence: 99%
“…(8,9). Previous studies have revealed the altered connectivity in patients with epilepsy (11) compared with healthy controls; however, the relationship between focal epileptogenicity and abnormal connectivity is unclear. (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation